Marketing Mix Development Guidelines for Pesticide Free Bananas: A Case Study of Ban Mae Khee Muk Community , Mae Cham District, Chiang Mai Province - Yawiraj , Sirirux (Community and Social Development Journal, 2020)
The objective of this research was to study the guidelines for the development of marketing mix for pesticide free bananas, a case study of Ban Mae Khee Muk Community , Mae Cham district in Chiang Mai province.The quantitative data was collected from 400 questionnaires and the qualitative data used in-depth interviews from 3 buyers. The findings revealed that the most popular banana is Kluai Nam Wa. The main buyers were divided into 2 main groups which were 1. Organizations who buy bananas for ingredients or to distribute in organizations such as schools and hospitals And 2. Consumer groups living in Mae Chaem district Chiang Mai province. Ripe bananas contain abundant nutrition which can be considered as an outstanding feature of bananas. The price is also cheaper than market and the quality can be developed to get a safety standard certification.